Promotion of rice seedling growth characteristics by development and use of bioformulation of Pseudomonas fluorescens - JAMBHULKAR, PRASHANT P; SHARMA, PRATIBHA (The Indian Journal of Agricultural Sciences, 2013)
The effect of various carrier based bioformulation was tested on germination, plant height, dry matter and yield. Theseed bacterisation increased seed germination by 4.1 to 11.7% over control in 2007–08 experiment and by 3.5 to 11.2% over control in 2008–09 in pot experiment and by 3.0 to 12.1% over control in 2007–08 experiment and by 2.0 to 11.8% over control in 2008-09 microplot experiment. Among all treatments seed bacterisation with talc based bioformulation increased plant height very significantly. Similarly these carrier based bioformulations increased dry matter and yield in a significant manner. Though the wheat and soybean based bioformulation was found ineffective in enhancing all growth parameters but talc and Kaolinite based bioformulation equally found at par to enhance plant growth characteristics.